Impact Kaizen Budget to reducing costs and continuous improvement the operations: study in General Company for Light Industries - Talib, Abbas Sabah (Journal of Economics and Administrative Sciences, 2021)
The budget represents a critical accounting tool used for planning and control. It is considered a measure of the results expected to occur. This study aims to identify the impact of the Kaizen Budget in reducing costs and continuous improvement on the General Company's operations for Light Industries. The research idea is based on the fact that preparing the budget based on constant improvement supports the higher management of people, processes, materials, and production methods, thus enabling them to manage and reduce their costs. Research results that the prepared budget suffers from many shortages that limit the materials' usefulness for management